A Study on Application of Comprehesive Rock Mechanical Properties and Geological Characteristics in Coal Mines - Yongjin S (The Australasian Institute of Mining and Metallurgy, 1992)
Datong coal Mine suffers from delays and sudden caving of its massive competent conglomerate roof. Detailed geological studies of the nature of pebbles and matrix of the conglomerate and its sparse bedding, joint and fracture structure, gave rise to investigation of water injection to destroy its strength and to control caving. Comparative investigations, including porisity, permeability, compressive strengths and water injection of conglomerate and sandstone led to empirical expressions relating various properties and to guidance for effective injection and caving practice. This new safe roof control practice should be even more improved with further research, including Modelling.